Negative electrode material and preparation method thereof, negative electrode plate, secondary battery and electric equipment

By using porous carbon substrates with specific pore length-to-diameter ratios and alternating deposition technology in lithium-ion batteries, longitudinal expansion of silicon particles is suppressed, and the volume expansion problem of silicon material in lithium-ion batteries is solved, and the cycle stability and electrochemical performance are improved.

CN119133397APending Publication Date: 2024-12-13HUBEI JIANGXIN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411256746.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, silicon as the negative electrode material, volume expansion and contraction during lithium-ion deliquefaction, resulting in material powdering and electrochemical performance degradation. The cyclic performance of existing silicon-carbon composite methods is still poor, especially in terms of longitudinal expansion. Effective means of inhibition.

Method used

By selecting the specific pore length-to-diameter ratio range and activation treatment of the porous carbon substrate, more longitudinal expansion buffer space is provided for nanosilicon particles, and by alternately deposition of silicon elements and doped elements, a carbon cladding layer is formed to reduce volume expansion against electrodes. The impact of materials.

Benefits of technology

It significantly improves the cycle stability and reversible specific capacity of the negative electrode material, extends the battery life, and has both high capacity and high first-term efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034320720000211
    Figure BDA0005034320720000211
  • Figure BDA0005034320720000231
    Figure BDA0005034320720000231
  • Figure BDA0005034320720000241
    Figure BDA0005034320720000241
Patent Text Reader

Abstract

The invention discloses a negative electrode material and a preparation method thereof, a negative electrode plate, a secondary battery and electrical equipment, the negative electrode material comprises a porous carbon substrate, a silicon element distributed in pores of the porous carbon substrate, and carbon coating the outer surfaces of the porous carbon substrate and the silicon element, and the length-diameter ratio A of the pores of the porous carbon substrate is selected from 1-200; the calculation formula of the length-diameter ratio A of the holes is as shown in formula (I), in the formula, L is the average diameter depth of the pore diameter in the porous carbon substrate, and the unit is nm; d is the average pore size of the porous carbon substrate, and the unit is nm. According to the invention, the length-diameter ratio of the porous carbon substrate is screened or the porous carbon substrate is activated and modified to reach a specific length-diameter ratio range, and more longitudinal expansion buffer space is provided for nano silicon particles with a relatively long hole longitudinal size, so that the influence of volume expansion on the electrode material can be effectively reduced, and the cycling stability of the electrode material is improved; and high capacity and high first efficiency are achieved. A = L / D (I).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and electrical equipment. Background Art

[0002] Silicon is currently the negative electrode material with the largest theoretical capacity, with a specific capacity of up to 4200mAh / g, which is much higher than the theoretical capacity of graphite (the theoretical capacity of graphite-based negative electrode materials is only 372mAh / g). Silicon has the advantages of low lithium insertion potential and low cost, and is expected to replace graphite as the next generation of lithium-ion battery negative electrode material. However, as a negative electrode material, silicon is accompanied by severe volume expansion and contraction during the lithium insertion and de-lithiation process, which makes the material easy to pulverize, fall off the current collector, and lose electrochemical performance.

[0003] Due to the structural stability of carbon materials, the volume change during charging and discharging is relatively small, and it has good cycle stability. In addition, due to the similar chemical properties to silicon, silicon and carbon are often compounded to achieve the purpose of improving the volume expansion effect of silicon and improving its electrochemical stability. However, the cycle performance of negative electrode materials obtained by existing silicon-carbon composite methods is still poor.

[0004] In the prior art, the hole size of porous carbon includes longitudinal and transverse dimensions, but most current technical solutions define the hole structure of porous carbon by transverse dimensions. For example, the Chinese invention patent document with application publication number CN 117416940 A discloses a porous carbon material and its preparation method and application, the preparation method comprising providing a porous carbon skeleton with an average pore size of 200-900nm; under the conditions of protective gas and a first gas phase carbon source, the porous carbon skeleton is subjected to a first gas phase deposition to obtain a porous carbon material with an average pore size less than or equal to 10nm. In this method, by regulating the pore structure, a porous carbon material with an average pore size less than 10nm is obtained to effectively control the growth of silicon nuclei and provide a buffer space for the volume expansion of silicon.

[0005] However, there is no good measurement for the longitudinal dimension at present. The volume expansion of silicon includes longitudinal and lateral expansion, and the longitudinal expansion is often the first to break (breaking through the carbon coating layer). Therefore, how to effectively suppress the longitudinal volume expansion of silicon particles is particularly critical. There are no research reports in this regard. Summary of the invention

[0006] In view of the above problems, the present invention discloses a negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and electrical equipment. By screening the aspect ratio of the porous carbon substrate, or activating and modifying the porous carbon substrate to reach a specific aspect ratio range, the nano-silicon particles are given more buffer space for longitudinal expansion with a longer longitudinal size of the pores, which can effectively reduce the effect of volume expansion on the electrode material, improve its cycle stability, and have both high capacity and high initial efficiency.

[0007] To achieve the above purpose, the specific technical solution of the present invention is as follows:

[0008] In a first aspect, the present invention provides a negative electrode material, comprising a porous carbon substrate, silicon elements distributed in the pores of the porous carbon substrate, and carbon coated on the outer surface of the porous carbon substrate and the silicon elements;

[0009] The pore aspect ratio A of the porous carbon substrate is selected from 1 to 200; the calculation formula of the pore aspect ratio A is as follows (I):

[0010] A=L / D (Ⅰ);

[0011] In formula (I), L is the average diameter depth of the pores in the porous carbon substrate, in nm; D is the average pore diameter of the porous carbon substrate, in nm.

[0012] In an optional embodiment, the calculation formula of the average diameter depth L of the pore diameter is as follows (II):

[0013] L=VD×10 3 / (SD—4V×10 3 ) (Ⅱ);

[0014] In formula (II), V is the pore volume of the porous carbon substrate, in cm 3 / g;

[0015] S is the specific surface area of ​​the porous carbon substrate, in m 2 / g.

[0016] In an optional embodiment, the porous carbon substrate satisfies at least one of the following A to F:

[0017] A. The average particle size D50 of the porous carbon substrate is selected from 0.5 to 30 μm, and the sphericity of the porous carbon substrate is Selected from 0.5 to 1.0;

[0018] B. The pore volume V of the porous carbon substrate is selected from 0.5 to 1.5 cm 3 / g, optionally, the pore volume V is selected from 0.5 to 1.2 cm 3 / g;

[0019] C. The specific surface area S of the porous carbon substrate is selected from 500 to 2500 m 2 / g;

[0020] D. The average pore size D of the porous carbon substrate is selected from 1 to 20 nm, and optionally, the average pore size D is selected from 1 to 15 nm;

[0021] E. A porous carbon substrate with a microporosity of no more than 50 vol%, a mesoporosity of 50-100 vol%, and a macroporosity of no more than 10 vol%; optionally, the mesoporosity is 70-100 vol%.

[0022] The present invention has found in a large number of experiments that a carbon substrate with a larger aspect ratio provides sufficient expansion space for nano silicon particles. During the charge and discharge process of a lithium battery, the nano silicon particles will undergo significant volume expansion, especially longitudinal expansion. Longitudinal expansion often causes the surface carbon coating to rupture, exposing the deposited nano silicon particles to contact the electrolyte, causing the SEI film of the negative electrode material to continuously rupture and rebuild, consuming the lithium source in the electrolyte, resulting in an increase in the irreversible capacity of charge and discharge, reducing the charge and discharge efficiency of the electrode, and shortening the service life of the battery; a longer aspect ratio can effectively alleviate this problem, allowing the nano silicon particles to fully stretch during expansion, avoiding the mechanical stress caused by insufficient space, and improving the comprehensive electrochemical performance of the battery.

[0023] In an optional embodiment, the pore aspect ratio A of the porous carbon substrate is selected from 30-150; more optionally, the pore aspect ratio A is selected from 70-150.

[0024] In an optional embodiment, the carbon coating layer in the negative electrode material has a content of 0.5 to 10 wt % and an average thickness of 1 to 50 nm; alternatively, the content is 2 to 5 wt % and the average thickness is 1 to 10 nm;

[0025] And / or, the silicon content in the negative electrode material is 30-80wt%, and the crystal domain size of the nano silicon particles is 0.1-5.0nm;

[0026] And / or, the specific surface area of ​​the negative electrode material is ≤50m 2 / g, optionally, specific surface area ≤10m 2 / g;

[0027] And / or, the average particle size D50 of the negative electrode material is 1.0 to 20.0 μm; optionally, D50 is 5.0 to 12.0 μm;

[0028] And / or, the resistivity of the negative electrode material is not greater than 100Ω·cm; optionally, the resistivity is not greater than 50Ω·cm;

[0029] And / or, the tap density of the negative electrode material is 0.5 to 2.0 g / cm3 .

[0030] In an optional embodiment, doping elements are also distributed in the pores of the porous carbon substrate.

[0031] In an optional embodiment, the doping element is selected from one or more of carbon, phosphorus, oxygen, nitrogen, and sulfur; optionally, the doping element is selected from one or more of carbon, phosphorus, nitrogen, and sulfur.

[0032] In an optional embodiment, the carbon is coated on the outer surface of the porous carbon substrate, the silicon element and the doping element.

[0033] In an optional embodiment, the content of the doping element in the negative electrode material is 0.1 to 10 wt %; optionally, the content of the doping element is 1 to 10 wt %.

[0034] In a second aspect, the present invention also provides a method for preparing the aforementioned negative electrode material:

[0035] In an optional embodiment, it includes:

[0036] Silicon deposition, placing the porous carbon substrate in a raw gas environment containing silicon source gas, performing vapor deposition, and obtaining a porous carbon substrate loaded with nano-silicon particles;

[0037] Coating treatment, placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a negative electrode material;

[0038] In an optional embodiment, the silicon is deposited at a temperature of 300-1200°C; optionally, the temperature is 500-800°C.

[0039] In an optional embodiment, the silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane and trichlorosilane.

[0040] In an optional embodiment, the volume proportion of the silicon source gas in the raw material gas containing the silicon source gas is 50-100%.

[0041] In an optional embodiment, the raw material gas containing the silicon source gas further comprises an inert gas as a carrier gas.

[0042] In an optional embodiment, the inert gas is selected from conventional types in the art, such as argon, helium, and the like.

[0043] In an optional embodiment, the volume proportion of the silicon source gas in the raw material gas containing the silicon source gas is 50 to 99%; optionally, the proportion is 50 to 80 vol%.

[0044] In an optional embodiment, the flow rate of the raw material gas containing the silicon source gas is 1 to 20 L / min; optionally, the flow rate is 5 to 15 L / min.

[0045] In an optional embodiment, the coating treatment is performed at a temperature of 300 to 1200°C; optionally, the temperature is 500 to 800°C.

[0046] In an optional embodiment, the carbon source gas is selected from alkane gases whose cracking temperature is within the carbon deposition temperature range, such as common types such as ethylene and acetylene.

[0047] In an optional embodiment, the volume proportion of the carbon source gas in the raw gas containing the carbon source gas is 70-100%.

[0048] In an optional embodiment, the raw material gas containing the carbon source gas further comprises an inert gas as a carrier gas.

[0049] In an optional embodiment, the inert gas is selected from conventional types in the art, such as argon, helium, and the like.

[0050] In an optional embodiment, the volume proportion of the silicon source gas in the raw gas containing the carbon source gas is 70 to 99%; optionally, the proportion is 70 to 80 vol%.

[0051] In an optional embodiment, the flow rate of the raw gas containing the carbon source gas is 1 to 20 L / min; optionally, the flow rate is 5 to 15 L / min.

[0052] When the doping element deposition is also performed simultaneously, in an optional embodiment, the method for preparing the negative electrode material includes:

[0053] Silicon deposition, placing the porous carbon substrate in a raw gas environment containing silicon source gas, performing vapor deposition, and obtaining a porous carbon substrate loaded with nano-silicon particles;

[0054] Doping element deposition, placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing doping element gas, and performing vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles and doping element particles;

[0055] Repeating silicon deposition and doping element deposition several times;

[0056] The coating treatment is to place the porous carbon substrate loaded with nano-silicon particles and doped element particles in a raw gas environment containing a carbon source gas, and perform vapor deposition to obtain a negative electrode material.

[0057] The silicon deposition process and the coating process are exactly the same as those of the aforementioned process of only performing silicon deposition.

[0058] In an optional embodiment, the doping element is deposited at a temperature of 300-1200°C; optionally, the temperature is 500-800°C.

[0059] In an optional embodiment, the doping element gas is selected from one or more of a carbon-containing gas, a phosphorus-containing gas, an oxygen-containing gas, a nitrogen-containing gas, and a sulfur-containing gas;

[0060] In an optional embodiment, the carbon-containing gas is selected from an alkane gas having a cracking temperature within the doping element deposition temperature range to provide carbon atoms.

[0061] In an optional embodiment, the phosphorus-containing gas is selected from one or more of phosphine, phosphorus chloride, and phosphorus fluoride to provide phosphorus atoms.

[0062] In an optional embodiment, the oxygen-containing gas is selected from one or more of oxygen, carbon monoxide, carbon dioxide, ethanol gas, and isopropanol gas to provide oxygen atoms.

[0063] In an optional embodiment, the nitrogen-containing gas is selected from ammonia; to provide nitrogen atoms.

[0064] In an optional embodiment, the sulfur-containing gas is selected from one or more of hydrogen sulfide, sulfur dioxide, and sulfur hexafluoride to provide sulfur atoms.

[0065] In an optional embodiment, the volume proportion of the carbon source gas in the raw gas containing the carbon source gas is 50-100%.

[0066] In an optional embodiment, the raw material gas containing the doping element gas further includes an inert gas as a carrier gas.

[0067] In an optional embodiment, the inert gas is selected from conventional types in the art, such as argon, helium, and the like.

[0068] In an optional embodiment, the volume proportion of the doping element gas in the raw material gas containing the doping element gas is 50-99%; optionally, the proportion is 50-80 vol%.

[0069] In an optional embodiment, the flow rate of the raw material gas containing the doping element is 1 to 20 L / min; optionally, the flow rate is 5 to 15 L / min.

[0070] During silicon deposition, when the pore aspect ratio A of the porous carbon substrate is not between 1 and 200, the porous carbon substrate needs to be activated.

[0071] In an optional embodiment, the activation treatment specifically includes:

[0072] The porous carbon substrate is placed in a reactor, and after vacuuming, an activating agent is introduced to perform an activation treatment, wherein the activation treatment satisfies at least one of the following a to d:

[0073] a. The activating agent is selected from water vapor;

[0074] b. The flow rate of the activator is 0.1 to 20 kg / h; optionally, the flow rate of the activator is 5 to 15 kg / h;

[0075] c. The activation treatment is performed at a temperature of 500 to 1200°C; optionally, at a temperature of 650 to 1000°C;

[0076] d. The activation treatment lasts for 0.5 to 2.0 hours; optionally, the activation treatment lasts for 0.5 to 1.5 hours.

[0077] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned negative electrode material or the negative electrode material prepared by the above-mentioned method.

[0078] In a fourth aspect, the present invention further provides a secondary battery, comprising the above-mentioned negative electrode plate.

[0079] In a fifth aspect, the present invention further provides an electrical device, comprising the above-mentioned secondary battery.

[0080] Compared with the prior art, the present invention has the following beneficial results:

[0081] The negative electrode material disclosed in the present invention selects porous carbon with a pore aspect ratio within a limited range as a substrate, or activates the porous carbon substrate that does not meet the requirements, so as to provide more buffer space for longitudinal expansion of nano silicon particles subsequently dispersed in the pores of the porous carbon substrate with a longer longitudinal pore size; and utilizes the high theoretical specific capacity of silicon, and arranges a carbon coating layer on the outer surface of the inner core to alleviate the volume expansion of the silicon-carbon negative electrode material during use and improve the conductivity, so as to obtain a negative electrode material with excellent cycle stability, high reversible specific capacity and high initial efficiency.

[0082] The present invention also uniformly deposits silicon and doping elements in the pores of the porous carbon substrate by alternately depositing silicon and doping elements, and isolates the deposited nano-silicon particles with doping atoms, effectively reducing the longitudinal size of the nano-silicon deposition, and avoiding the nano-silicon particles from contacting again inside the pores to expand the particle size during the battery cycle after the electrode is prepared, thereby amplifying their expansion effect, effectively avoiding the rupture of the outer coating layer due to excessive longitudinal expansion of the nano-silicon particles, and the contact of active particles with the electrolyte to cause more capacity loss and even safety hazards, which can effectively reduce the influence of volume expansion on the electrode material and improve the cycle stability; due to the introduction of doping elements, it is also beneficial to increase the ion and electron transmission rate.

[0083] The present invention effectively suppresses the volume expansion of nano-silicon particles during lithium insertion and extraction through the design of a porous carbon substrate and the introduction of doping elements, thereby improving the cycle performance of the negative electrode material. DETAILED DESCRIPTION

[0084] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0085] An embodiment of the present invention provides a negative electrode material, comprising a porous carbon substrate, silicon elements distributed in the pores of the porous carbon substrate, and carbon coated on the outer surface of the porous carbon substrate and the silicon elements;

[0086] The pore aspect ratio A of the porous carbon substrate is selected from 1 to 200; the calculation formula of the pore aspect ratio A is as follows (I):

[0087] A=L / D (Ⅰ);

[0088] In formula (I), L is the average diameter depth of the pores in the porous carbon substrate, in nm; D is the average pore diameter of the porous carbon substrate, in nm.

[0089] The pore aspect ratio A can specifically be 1, 5, 10, 30, 70, 100, 120, 150, 180, 200 or any value in the range of 1 to 200; by adopting a porous carbon substrate with a higher pore aspect ratio, this pore structure can provide more buffer space for the longitudinal volume expansion of nano-silicon particles in the pores due to the elongated longitudinal dimension, so that the silicon expansion has less impact on the substrate and the coating layer, and effectively reduces the impact of volume expansion on the electrode material; optionally, A is selected from 30 to 150; more optionally, the pore aspect ratio A is selected from 70 to 150.

[0090] In an optional embodiment, the calculation formula of the average diameter depth L of the pore diameter is as follows (II):

[0091] L=VD×10 3 / (SD—4V×10 3 ) (Ⅱ);

[0092] In formula (II), V is the pore volume of the porous carbon substrate, in cm 3 / g;

[0093] S is the specific surface area of ​​the porous carbon substrate, in m 2 / g.

[0094] Among them, the specific surface area, pore volume and pore diameter are all tested by the Micromeritics 3020 instrument.

[0095] In an optional embodiment, the porous carbon substrate satisfies at least one of the following A to E:

[0096] A. The average particle size D50 of the porous carbon substrate is selected from 0.5 to 30 μm, and specifically can be 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm or any value between 0.5 μm and 30 μm.

[0097] B. The pore volume V of the porous carbon substrate is selected from 0.5 to 1.5 cm 3 / g, specifically 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1.0cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g or any value within the above range; optionally, the pore volume V is selected from 0.5 to 1.2 cm 3 / g; more optionally, the pore volume V is selected from 0.7 to 1.0 cm 3 / g.

[0098] C. The specific surface area S of the porous carbon substrate is selected from 500 to 2500 m 2 / g; specifically, 500m 2 / g, 600m 2 / g、800m 2 / g、1000m 2 / g、1200m 2 / g、1400m 2 / g、1600m 2 / g、1800m 2 / g, 2000m 2 / g, 2200m 2 / g、2500m 2 / g or any value within the above range.

[0099] D. The average pore diameter D of the porous carbon substrate is selected from 1 to 20 nm; specifically, it can be 1 nm, 3 nm, 5 nm, 8 nm, 12 nm, 15 nm, 18 nm, 20 nm or any value within the above range; optionally, the average pore diameter D is selected from 1 to 15 nm.

[0100] E. The porous carbon substrate has a microporosity of no more than 50 vol%, specifically 50 vol%, 40 vol%, 30 vol%, 20 vol%, 10 vol%, 5 vol%, 0 vol% or any value within the above range; a mesoporosity of 50-100 vol%, specifically 50 vol%, 60 vol%, 70 vol%, 80 vol%, 90 vol%, 100 vol% or any value within the above range; a macroporosity of no more than 10 vol%, specifically 10 vol%, 8 vol%, 5 vol%, 0 vol% or any value within the above range; optionally, a mesoporosity of 70-100 vol%. The higher mesoporosity makes the deposited silicon nanoparticles restricted by the pore structure, have a very small particle size (silicon domain <5 nm), and correspondingly reduce the absolute volume expansion, which is conducive to improving the coulombic efficiency while ensuring high stability.

[0101] In an optional embodiment, the carbon coating content in the negative electrode material is 0.5-10wt%, specifically 0.5wt%, 1wt%, 2wt%, 5wt%, 7wt%, 9wt%, 10wt% or any value within the above range; the carbon coating is beneficial to further alleviate the volume expansion of the negative electrode material during the lithium insertion process and improve the conductivity. Optionally, the carbon coating content is 2-5wt%.

[0102] In an optional embodiment, the average thickness of the carbon coating layer in the negative electrode material is 1 to 50 nm; specifically, it can be 1 nm, 2 nm, 5 nm, 7 nm, 9 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm or any value within the above range; too thick a carbon coating layer is not conducive to the improvement of the specific capacity of the negative electrode material, and since the carbon coating layer is denser than the core, too thick a carbon coating layer is not conducive to the migration of lithium ions. Optionally, the average thickness of the carbon coating layer is 1 to 10 nm. More optionally, the average thickness of the carbon coating layer is 1 to 5 nm.

[0103] In an optional embodiment, the silicon content in the negative electrode material is 30-80wt%; specifically, it can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt% or any value within the above range; increasing the silicon content in the negative electrode material is beneficial to improving the capacity of the negative electrode material, but because silicon as a negative electrode material is accompanied by severe volume expansion and contraction during the lithium insertion and delithiation process, it will affect the cycle performance of the negative electrode material, so the silicon content should not be too much. Optionally, the silicon content is 40-60wt%.

[0104] In an optional embodiment, the crystal domain size of the nano silicon particles in the negative electrode material is 0.1 to 5.0 nm; specifically, it can be 0.1 nm, 0.5 nm, 1 nm, 3 nm, 5 nm or any value within the above range; small particles can effectively reduce the degree of volume expansion, which is beneficial to improving the cycle stability performance.

[0105] In an optional embodiment, the specific surface area of ​​the negative electrode material is ≤50m 2 / g; specifically, it can be 1m 2 / g, 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g or any value within the above range, the increase in specific surface area can increase the number of active sites for lithium insertion and extraction, which is beneficial to lithium insertion and extraction, but too large a specific surface area is not conducive to improving the cycle performance of the negative electrode material. Optionally, the specific surface area ≤10m 2 / g.

[0106] In an optional embodiment, the average particle size D50 of the negative electrode material is 1.0-20.0 μm; specifically, it can be 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 20 μm or any value within the above range. If the particle size of the negative electrode material is too large, the path for lithium deintercalation at the center will increase, and the difficulty of lithium deintercalation will increase. Optionally, D50 is 5.0-12.0 μm.

[0107] In an optional embodiment, the resistivity of the negative electrode material is not greater than 100Ω·cm; specifically, it can be 100Ω·cm, 90Ω·cm, 80Ω·cm, 70Ω·cm, 60Ω·cm, 50Ω·cm, 40Ω·cm, 30Ω·cm, 20Ω·cm, 10Ω·cm, 5Ω·cm, 1Ω·cm or any value within the above range; optionally, the resistivity is not greater than 50Ω·cm; more optionally, the resistivity is not greater than 10Ω·cm.

[0108] In an optional embodiment, the tap density of the negative electrode material is 0.5 to 2.0 g / cm 3 ; Specifically, it can be 0.5g / cm 3 , 0.8g / cm 3 , 1.1g / cm 3 , 1.4g / cm 3, 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 Or any value within the above range, increasing the tap density is beneficial to improving the energy density of the material, but too high a tap density will reduce the pore structure and increase the difficulty of lithium insertion and extraction. Optionally, the tap density is 0.7-1.5 g / cm 3 .

[0109] In an optional embodiment, doping elements are also distributed in the pores of the porous carbon substrate. The introduction of doping elements is conducive to further reducing the longitudinal size of the nano-silicon particles, improving the cycle stability, and at the same time increasing the conductivity and reducing the resistivity.

[0110] In an optional embodiment, the doping element is selected from one or more of carbon, phosphorus, oxygen, nitrogen, and sulfur; optionally, the doping element is selected from one or more of carbon, phosphorus, nitrogen, and sulfur.

[0111] In an optional embodiment, the carbon is coated on the outer surface of the porous carbon substrate, the silicon element and the doping element.

[0112] In an optional embodiment, the content of the doping element in the negative electrode material is 0.1 to 10 wt%; specifically, it can be 0.1 wt%, 1 wt%, 2 wt%, 5 wt%, 7 wt%, 9 wt%, 10 wt% or any value within the above range. The introduction of a proper amount of doping elements into the negative electrode material is beneficial to improving the conductivity of the negative electrode material. However, since excessive incorporation of doping elements will affect the cycle performance of the negative electrode material, the content of the doping elements should not be too much. Optionally, the content of the doping element is 1 to 10 wt%.

[0113] In a second aspect, the present invention also provides a method for preparing the aforementioned negative electrode material:

[0114] In an optional embodiment, it includes:

[0115] Silicon deposition, placing the porous carbon substrate in a raw gas environment containing silicon source gas, performing vapor deposition, and obtaining a porous carbon substrate loaded with nano-silicon particles;

[0116] The coating treatment is to place the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and perform vapor deposition to obtain a negative electrode material.

[0117] In an optional embodiment, the silicon is deposited at a temperature of 300-1200°C; specifically, it can be 300°C, 500°C, 700°C, 900°C, 1200°C or any value within the above range; optionally, the temperature is 500-800°C.

[0118] In an optional embodiment, the silicon source gas is selected from one or more of monosilane, disilane, dichlorosilane and trichlorosilane.

[0119] In an optional embodiment, the volume proportion of the silicon source gas in the raw gas containing silicon source gas is 50-100%; specifically, it can be 50%, 60%, 70%, 80%, 90%, 100% or any value within the above range.

[0120] In an optional embodiment, the raw material gas containing the silicon source gas further comprises an inert gas as a carrier gas.

[0121] In an optional embodiment, the inert gas is selected from conventional types in the art, such as argon, helium, and the like.

[0122] In an optional embodiment, the volume proportion of the silicon source gas in the raw material gas containing the silicon source gas is 50 to 99%; optionally, the proportion is 50 to 80 vol%.

[0123] In an optional embodiment, the flow rate of the raw gas containing silicon source gas is 1 to 20 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min, 20 L / min or any value within the above range; optionally, the flow rate is 5 to 15 L / min.

[0124] In an optional embodiment, the coating treatment is carried out at a temperature of 300-1200°C; specifically, it can be 300°C, 500°C, 700°C, 900°C, 1200°C or any value within the above range; optionally, the temperature is 500-800°C.

[0125] In an optional embodiment, the carbon source gas is selected from alkane gases whose cracking temperature is within the carbon deposition temperature range, such as common types such as ethylene and acetylene.

[0126] In an optional embodiment, the volume proportion of the carbon source gas in the raw gas containing the carbon source gas is 70-100%; specifically, it can be 70%, 75%, 80%, 85%, 90%, 95%, 100% or any value within the above range.

[0127] In an optional embodiment, the raw material gas containing the carbon source gas further comprises an inert gas as a carrier gas.

[0128] In an optional embodiment, the inert gas is selected from conventional types in the art, such as argon, helium, and the like.

[0129] In an optional embodiment, the volume proportion of the silicon source gas in the raw gas containing the carbon source gas is 70 to 99%; optionally, the proportion is 70 to 80 vol%.

[0130] In an optional embodiment, the flow rate of the raw gas containing carbon source gas is 1 to 20 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min, 20 L / min or any value within the above range; optionally, the flow rate is 5 to 15 L / min.

[0131] When the doping element deposition is also performed simultaneously, in an optional embodiment, the method for preparing the negative electrode material includes:

[0132] Silicon deposition, placing the porous carbon substrate in a raw gas environment containing silicon source gas, performing vapor deposition, and obtaining a porous carbon substrate loaded with nano-silicon particles;

[0133] Doping element deposition, placing the porous carbon substrate loaded with nano silicon particles in a raw gas environment containing doping element gas, and performing vapor deposition to obtain a porous carbon substrate loaded with nano silicon particles and doping element particles.

[0134] The silicon deposition and the doping element deposition are repeated several times.

[0135] In an optional embodiment, the number of times is 2 to 10 times; specifically, it can be 2, 3, 4, 5, 6, 7, 8, 9, 10 or any value within the above range.

[0136] The coating treatment is to place the porous carbon substrate loaded with nano-silicon particles and doped element particles in a raw gas environment containing a carbon source gas, and perform vapor deposition to obtain a negative electrode material.

[0137] The silicon deposition process and the coating process are exactly the same as those of the aforementioned process of only performing silicon deposition.

[0138] In an optional embodiment, the doping element is deposited at a temperature of 300-1200°C; specifically, it can be 300°C, 500°C, 700°C, 900°C, 1200°C or any value within the above range; optionally, the temperature is 500-800°C.

[0139] In an optional embodiment, the doping element gas is selected from one or more of a carbon-containing gas, a phosphorus-containing gas, an oxygen-containing gas, a nitrogen-containing gas, and a sulfur-containing gas.

[0140] In an optional embodiment, the carbon-containing gas is selected from an alkane gas having a cracking temperature within the doping element deposition temperature range to provide carbon atoms.

[0141] In an optional embodiment, the phosphorus-containing gas is selected from one or more of phosphine, phosphorus chloride, and phosphorus fluoride to provide phosphorus atoms.

[0142] In an optional embodiment, the oxygen-containing gas is selected from one or more of oxygen, carbon monoxide, carbon dioxide, ethanol gas, and isopropanol gas to provide oxygen atoms.

[0143] In an optional embodiment, the nitrogen-containing gas is selected from ammonia; to provide nitrogen atoms.

[0144] In an optional embodiment, the sulfur-containing gas is selected from one or more of hydrogen sulfide, sulfur dioxide, and sulfur hexafluoride to provide sulfur atoms.

[0145] In an optional embodiment, the volume proportion of the carbon source gas in the raw gas containing the carbon source gas is 50-100%; specifically, it can be 50%, 60%, 70%, 80%, 90%, 100% or any value within the above range.

[0146] In an optional embodiment, the raw material gas containing the doping element gas further includes an inert gas as a carrier gas.

[0147] In an optional embodiment, the inert gas is selected from conventional types in the art, such as argon, helium, and the like.

[0148] In an optional embodiment, the volume proportion of the doping element gas in the raw material gas containing the doping element gas is 50-99%; optionally, the proportion is 50-80 vol%.

[0149] In an optional embodiment, the flow rate of the raw gas containing the doping element is 1 to 20 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min, 20 L / min or any value within the above range; optionally, the flow rate is 5 to 15 L / min.

[0150] During silicon deposition, when the pore aspect ratio A of the porous carbon substrate is not between 1 and 200, the porous carbon substrate needs to be activated.

[0151] In an optional embodiment, the activation treatment specifically includes:

[0152] The porous carbon substrate is placed in a reactor, and after evacuation, an activating agent is introduced for activation treatment, wherein the activation treatment satisfies at least one of the following a to d:

[0153] a. The activating agent is selected from water vapor.

[0154] b. The flow rate of the activator is 0.1 to 20 kg / h; specifically, it can be 0.1 kg / h, 1 kg / h, 2 kg / h, 3 kg / h, 4 kg / h, 5 kg / h, 6 kg / h, 7 kg / h, 8 kg / h, 9 kg / h, 10 kg / h, 11 kg / h, 12 kg / h, 13 kg / h, 14 kg / h, 15 kg / h, 16 kg / h, 17 kg / h, 18 kg / h, 19 kg / h, 20 kg / h or any value within the above range; optionally, the flow rate of the activator is 5 to 15 kg / h.

[0155] c. The activation treatment is performed at a temperature of 500 to 1200°C; specifically, it may be 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or any value within the above range; optionally, the temperature is 650 to 1000°C.

[0156] d. The activation treatment time is 0.5 to 2.0 h; specifically, it can be 0.5 h, 1.0 h, 1.5 h, 2.0 h or any value within the above range; optionally, the time is 0.5 to 1.5 h.

[0157] An embodiment of the present invention provides a negative electrode plate, comprising the negative electrode material mentioned above or the negative electrode material prepared by the method mentioned above.

[0158] An embodiment of the present invention provides a secondary battery, comprising the above-mentioned negative electrode plate.

[0159] An embodiment of the present invention provides an electrical device, including the secondary battery mentioned above.

[0160] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0161] Example 1

[0162] Activation treatment of porous carbon substrate:

[0163] The specific surface area of ​​100g is 680m 2 / g, pore volume is 0.66cm 3 / g, the average pore size is 5.22nm, and after calculation, the porous carbon substrate with a pore aspect ratio of 0.72 is placed in an activation furnace, the furnace temperature is adjusted to 800°C, vacuumed, and water vapor is introduced at a flow rate of 10kg / h for activation treatment. The treatment time is 1h to obtain a porous carbon substrate after activation treatment;

[0164] According to the BET test, the specific surface area of ​​the porous carbon substrate after activation treatment is 702.510 m 2 / g, average pore diameter of 5.25nm, pore volume of 0.920cm 3 / g, it is calculated that the pore aspect ratio of the porous carbon substrate after activation treatment is 112;

[0165] The pore size distribution was tested by nitrogen adsorption and desorption. The microporosity of the porous carbon substrate after activation treatment was 18.5 vol%, the mesoporosity was 77.8 vol%, and the macroporosity was 3.7 vol%; the average particle size D50 was 4.5 μm.

[0166] Silicon Deposition:

[0167] The activated porous carbon substrate was placed in a CVD furnace, the temperature of the deposition furnace was adjusted to 600°C, and monosilane gas and argon gas were introduced into the CVD furnace at a volume ratio of 4:1 at a total flow rate of 10 L / min, and the ventilation was continued for 1 hour;

[0168] Doping element deposition: After the deposition in the previous stage is completed, a mixed gas containing ammonia and argon (the volume ratio of ammonia to argon is 1:1) is introduced at a total flow rate of 5L / min and the ventilation is continued for 0.5h;

[0169] Alternately repeating silicon deposition and doping element deposition 8 times to obtain an intermediate product after vapor deposition;

[0170] Coating treatment:

[0171] The temperature of the CVD furnace was adjusted to 600°C, and a mixture of acetylene and argon (the volume ratio of acetylene to argon was 4:1) was introduced at a total flow rate of 5 L / min for high-temperature carbon coating. After continuous ventilation for 2 hours, the temperature was lowered to room temperature. The material was dispersed, screened, demagnetized, and other means to obtain the negative electrode material. The theoretical mass of the carbon coating layer was controlled to account for 3wt% of the mass of the final prepared negative electrode material.

[0172] According to tests, in the negative electrode material prepared in this embodiment, the carbon coating content is 3.2wt%, the silicon content is 50.3wt%, the content of the doping element N is 4.3wt%; the crystal domain size of the nano silicon particles is 3.79nm; and the average thickness of the carbon coating layer is 4nm.

[0173] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0174] Example 2

[0175] The preparation process is basically the same as that in Example 1, except that:

[0176] The activation treatment time in the activation treatment step of the porous carbon substrate was replaced with 1.5 h.

[0177] After testing, the specific surface area of ​​the activated porous carbon substrate is 719.630 m 2 / g, average pore diameter of 5.29nm, pore volume of 0.950cm 3 / g. After calculation, the pore aspect ratio of the porous carbon substrate after activation treatment is 139.

[0178] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0179] Example 3

[0180] The preparation process is basically the same as that in Example 1, except that:

[0181] The activation treatment time in the activation treatment step of the porous carbon substrate was replaced with 0.5 h.

[0182] After testing, the specific surface area of ​​the activated porous carbon substrate is 688.166m 2 / g, the average pore diameter is 5.22nm, and the pore volume is 0.895cm 3 / g, after calculation, the pore aspect ratio of the porous carbon substrate after activation treatment is 74.

[0183] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0184] Example 4

[0185] The preparation process is basically the same as that in Example 1, except that:

[0186] The ammonia gas in the dopant element deposition step was replaced by acetylene at an equal volume flow rate.

[0187] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0188] Example 5

[0189] The preparation process is basically the same as that in Example 1, except that:

[0190] The ammonia gas in the dopant element deposition step was replaced by phosphine at an equal volume flow rate.

[0191] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0192] Example 6

[0193] The preparation process is basically the same as that in Example 1, except that:

[0194] The ammonia gas in the dopant element deposition step was replaced by carbon dioxide at an equal volume flow rate.

[0195] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0196] Example 7

[0197] The preparation process is basically the same as that in Example 1, except that:

[0198] The ammonia gas in the doping element deposition step is replaced by hydrogen sulfide at an equal volume flow rate.

[0199] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0200] Example 8

[0201] The preparation process is basically the same as that in Example 1, except that:

[0202] The continuous aeration time in the silicon deposition step was replaced with 2 h;

[0203] The number of alternating depositions of silicon deposition and doping element deposition is replaced to 5 times.

[0204] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0205] Example 9

[0206] The preparation process is basically the same as that in Example 1, except that:

[0207] Replace the continuous ventilation time in the doping element deposition step with 1 h;

[0208] The number of alternating depositions of silicon deposition and doping element deposition is replaced to 6 times.

[0209] The parameters such as the content of doping elements in the negative electrode material prepared in this embodiment, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in Table 1 below.

[0210] Example 10

[0211] The preparation process is basically the same as that in Example 1, except that:

[0212] The specific surface area of ​​the porous carbon substrate used is 1369m 2 / g, pore volume is 1.1cm 3 / g, the average pore diameter is 3.22nm, and the pore aspect ratio is calculated to be 134; and the porous carbon substrate is directly used for subsequent deposition without activation treatment.

[0213] Embodiment 11

[0214] The preparation process is basically the same as that in Example 1, except that:

[0215] The continuous ventilation time in the silicon deposition step was replaced with 8 hours, and the doping element deposition and the alternating deposition steps were not performed. That is, only silicon deposition was performed in this embodiment.

[0216] Comparative Example 1

[0217] The preparation process is substantially the same as that of Example 1, except that the porous carbon substrate is not activated, that is, the porous carbon substrate with a pore aspect ratio of 0.72 is directly used for subsequent deposition.

[0218] According to tests, the microporosity of the porous carbon substrate is 15.6 vol%, the mesoporosity is 71.7 vol%, and the macroporosity is 12.7 vol%; the average particle size D50 is 5 μm.

[0219] The parameters such as the content of doping elements in the negative electrode material prepared in this comparative example, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in the following Table 1.

[0220] Comparative Example 2

[0221] The preparation process is basically the same as that of Example 1, except that:

[0222] The activation treatment time in the activation treatment step of the porous carbon substrate was replaced with 2.5 h.

[0223] After testing, the specific surface area of ​​the activated porous carbon substrate is 739.285m 2 / g, average pore diameter of 5.39nm, pore volume of 0.995cm 3 / g, it is calculated that the pore aspect ratio of the porous carbon substrate after activation treatment is 210.

[0224] According to the test, the microporosity of the porous carbon substrate is 13.5 vol%, the mesoporosity is 80.1 vol%, and the macroporosity is 6.4 vol%.

[0225] The parameters such as the content of doping elements in the negative electrode material prepared in this comparative example, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in the following Table 1.

[0226] Comparative Example 3

[0227] The preparation process is basically the same as that in Example 1, except that:

[0228] Replace the continuous ventilation time in the doping element deposition step with 2 h;

[0229] The number of alternating depositions of silicon deposition and doping element deposition is replaced to 4 times.

[0230] The parameters such as the content of doping elements in the negative electrode material prepared in this comparative example, the specific surface area, average pore size, resistivity and tap density of the negative electrode material are specifically listed in the following Table 1.

[0231] The doping element content in Table 1 was tested by an element analyzer, the particle size was tested by Malvern 3000, the powder resistance was measured by a semiconductor powder resistivity tester (30 MPa four-probe V1.4), the tap density was measured by a tap density meter, and the specific surface area was tested by Micrometer 3020.

[0232] Table 1

[0233]

[0234] Application examples:

[0235] Batteries were assembled using the products prepared in each embodiment and each comparative example as negative electrode materials.

[0236] (1) Preparation of positive electrode sheets: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent SuperP, carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.

[0237] (2) Preparation of negative electrode sheets: Under a nitrogen protective atmosphere, the solvent N-methylpyrrolidone (NMP) and the binder PVDF were stirred and mixed, and then the conductive agent SuperP was added and stirred and mixed. Then, the products prepared in each embodiment and each comparative example were added as negative electrode active materials and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).

[0238] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.

[0239] (3) Assembly of lithium-ion batteries

[0240] Using PE porous polymer film as a separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrode sheets, and the bare battery cell is wound; the bare battery cell is placed in an aluminum plastic shell package, and dried at 100°C under a relative vacuum pressure of -0.95×105Pa until the moisture content is less than 100ppm. The electrolyte is injected into the dried bare battery cell, wherein the electrolyte is composed of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and the package, static, formation (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaping, and capacity testing (capacity separation) are performed to make a soft-pack liquid lithium-ion battery.

[0241] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.

[0242] The battery cycle performance is tested on the Xinwei equipment, specifically:

[0243] At 25°C, first discharge at 0.1C to 0.005V, then discharge at 0.08C to 0.001V, discharge at 0.05C to 0.001V, discharge at 0.02C to 0.001V, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, and calculate the capacity retention rate after 100 cycles. The test and calculation process of the capacity retention rate after 500 cycles adopt the same method. The specific test / calculation results are shown in Table 2 below.

[0244] Table 2

[0245]

[0246]

[0247] Comparing the data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 2, it can be seen that the porous substrate that does not meet the requirements is subjected to water vapor pore formation treatment. According to the data before and after the treatment of Example 1 (see Table 1 for details), the pore volume of the porous carbon substrate after water vapor pore formation increases significantly when the specific surface area and the average pore size change are small. It can be seen that the hole depth is extended, and adsorption pore formation can effectively adjust the hole depth, and then adjust the hole aspect ratio. When the hole aspect ratio is large, that is, the longitudinal dimension of the hole is long, the nano-silicon particles located in the pore channel have more longitudinal expansion buffer space, and the cycle stability is significantly improved; when the longitudinal dimension is too short, the porous carbon substrate significantly weakens the expansion restriction of the nano-silicon particles, and the cycle attenuation is obvious; when the longitudinal dimension is too long, the hole tends to be a through hole, the longitudinal stress is poor, and the nano-silicon particles will still break through the restriction of the carbon coating during the expansion process, and the cycle stability is significantly reduced.

[0248] Comparing the data of Examples 1, 4 to 7 and 11 in Table 2, it can be seen that the appropriate amount of doping elements significantly improves the cycle stability without affecting the reversible specific capacity and the first effect. This is because the doping elements can play an isolating role, further reducing the longitudinal size of the nano-silicon particles, and can also effectively improve the conductivity of the negative electrode material (see Table 1 for details); relative to other element doping, the reversible specific capacity of the secondary battery assembled by the negative electrode material prepared by oxygen doping is more significantly reduced. Comparing Example 1 with Comparative Example 3, it can be found that with the excessive increase of doping elements, the reversible specific capacity is seriously affected, and then the coulomb efficiency is affected. This may be due to the excessive combination of non-metallic elements with nano-silicon particles, which is not conducive to subsequent use.

[0249] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.

Claims

1. A negative electrode material, comprising a porous carbon substrate, silicon distributed in the pores of the porous carbon substrate, and carbon coated on the outer surface of the porous carbon substrate and the silicon, characterized in that: The pore aspect ratio A of the porous carbon substrate is selected from 1 to 200; the calculation formula of the pore aspect ratio A is as follows (I): A=L / D (Ⅰ); In formula (I), L is the average diameter depth of the pores in the porous carbon substrate, in nm; D is the average pore diameter of the porous carbon substrate, in nm.

2. The negative electrode material according to claim 1, characterized in that The calculation formula of the average diameter depth L of the pore diameter is as follows (II): L=VD×10 3 / (SD—4V×10 3 ) (Ⅱ); In formula (II), V is the pore volume of the porous carbon substrate, in cm 3 / g; S is the specific surface area of ​​the porous carbon substrate, in m 2 / g.

3. The negative electrode material according to claim 1, characterized in that The porous carbon substrate satisfies at least one of the following A to E: A. The average particle size D50 of the porous carbon substrate is selected from 0.5 to 30 μm; B. The pore volume V of the porous carbon substrate is selected from 0.5 to 1.5 cm 3 / g, optionally, the pore volume V is selected from 0.5 to 1.2 cm 3 / g; C. The specific surface area S of the porous carbon substrate is selected from 500 to 2500 m 2 / g; D. The average pore size D of the porous carbon substrate is selected from 1 to 20 nm, and optionally, the average pore size D is selected from 1 to 15 nm; E. A porous carbon substrate with a microporosity of no more than 50 vol%, a mesoporosity of 50-100 vol%, and a macroporosity of no more than 10 vol%; optionally, the mesoporosity is 70-100 vol%.

4. The negative electrode material according to claim 1, characterized in that The carbon coating layer in the negative electrode material has a content of 0.5 to 10 wt % and an average thickness of 1 to 50 nm; optionally, the content is 2 to 5 wt % and the average thickness is 1 to 10 nm; And / or, the silicon content in the negative electrode material is 30-80wt%, and the crystal domain size of the nano silicon particles is 0.1-5.0nm; And / or, the specific surface area of ​​the negative electrode material is ≤50m 2 / g, optionally, specific surface area ≤10m 2 / g; And / or, the average particle size D50 of the negative electrode material is 1.0 to 20.0 μm; optionally, D50 is 5.0 to 12.0 μm; And / or, the resistivity of the negative electrode material is not greater than 100Ω·cm; optionally, the resistivity is not greater than 50Ω·cm; And / or, the tap density of the negative electrode material is 0.5 to 2.0 g / cm 3 .

5. The negative electrode material according to claim 1, characterized in that Doping elements are also distributed in the pores of the porous carbon substrate; The doping element is selected from one or more of carbon, phosphorus, oxygen, nitrogen and sulfur; The carbon is coated on the outer surface of the porous carbon substrate, the silicon element and the doping element; The content of the doping element in the negative electrode material is 0.1 to 10 wt %; optionally, the content of the doping element is 1 to 10 wt %.

6. A method for preparing a negative electrode material according to any one of claims 1 to 5, characterized in that: include: Silicon deposition, placing the porous carbon substrate in a raw gas environment containing silicon source gas, performing vapor deposition, and obtaining a porous carbon substrate loaded with nano-silicon particles; Coating treatment, placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a negative electrode material; Or: Silicon deposition, placing the porous carbon substrate in a raw gas environment containing silicon source gas, performing vapor deposition, and obtaining a porous carbon substrate loaded with nano-silicon particles; Doping element deposition, placing the porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing doping element gas, and performing vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles and doping element particles; Repeating silicon deposition and doping element deposition several times; The coating treatment is to place the porous carbon substrate loaded with nano-silicon particles and doped element particles in a raw gas environment containing a carbon source gas, and perform vapor deposition to obtain a negative electrode material.

7. The method for preparing the negative electrode material according to claim 6, characterized in that: During silicon deposition, when the pore aspect ratio A of the porous carbon substrate is not between 1 and 200, the porous carbon substrate is activated, specifically comprising: The porous carbon substrate is placed in a reactor, and after vacuuming, an activating agent is introduced to perform an activation treatment, wherein the activation treatment satisfies at least one of the following a to d: a. The activating agent is selected from water vapor; b. The flow rate of the activator is 0.1 to 20 kg / h; c. The activation treatment temperature is 500 to 1200 ° C; d. The activation treatment time is 0.5 to 2.0 hours.

8. A negative electrode plate, characterized in that: The invention comprises the negative electrode material as claimed in any one of claims 1 to 5 or the negative electrode material prepared by the method as claimed in claim 6 or 7.

9. A secondary battery, characterized in that: Comprising the negative electrode sheet as described in claim 8.

10. An electrical device comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • A preparation method of silicon-carbon composite material for negative electrode of lithium ion battery

    CN109244377A

  • Preparation method of novel silicon-carbon negative electrode material and product thereof

    CN116613299A

  • Pre-lithium silicon carbon negative electrode material as well as preparation method and application thereof

    CN117199287A

  • Silicon carbon electrode material and preparation method and application thereof

    CN117673333A

  • Negative electrode material, preparation method thereof and battery

    CN118016866A

Cited By

  • Silicon carbon material and secondary battery comprising same

    CN119695121A

  • Porous carbon material, negative electrode material, negative electrode plate, secondary battery and preparation method of secondary battery

    CN119954155A